Tipologia di donne nella "Vita S. Pauli monachi Thebaei" di san Girolamo - Degórski, Bazyli (Vox Patrum, 2020)
In the historical monastic literature, the presence of the feminine figure is sparse and few. In itself the presence of women must be exorcised, at least if we do not treat sinners to be converted or of pious ones who ask for grace and miracles. The figure of the sister of the ascetic is the most common, following the model of the Vita S. Antonii, written by St. Athanasius of Alexandria. St. Jerome in his Vita S. Pauli Primi Eremitae monachi Thebaei follows this classic canon, but later for the Vita S. Hilarionis and even for the Vita S. Malchi monachi captivi overcomes the dominant genre and dares novelty, rather autobiographically. In the Vita S. Pauli Primi Eremitae monachi Thebaei the female figure appears in three types and all are negative: a prostitute, the instrument of martyrdom; a nod to Cleopatra, pagan and of morally condemnable conduct; and the sister of the ascetic, fragile, submissive to her husband, and of bland personality. The woman, therefore, is presented as an “evil” when she looks under any dress in the life of the monk. Temptress, historical or family character she is always to be exorcised as presence.